Environmental auditing practices: understanding the flow between two Malaysian local governments - Mohd Jamil, Muthyaah; Zainal Abidin, Nor Hafizah; Mohd Alwi, Norhayati (Human Resource Management Academic Research Society, 2022)
In 2015, the United Nation Sustainable Development Goals (SDGs) issued 17 initiatives comprising environmental, social and eco nomic initiatives. It leads to the implementation the environmental auditing practices (INTOSAI, 2006). However, there is no one process for the implementation of environmental auditing practices. The purpose of this study is to highlight the flow of envir onmental auditing practices (EAP) in two Malaysian Local Governments (MLG). This study used an interpretative qualitative study from two Malaysian Local Governments. This study analysed 272 documents which comprise transcribed interviews, regulatory docume nt and notes from observations This study concludes that EAP is more dynamic in ALPHA than BETA. It is due to the composition of the audit process and determining the objectives of the EAP. The study showed that the adoption of ISO 14001, the standard for managing the environmental program may ease the operation of auditing environmental programs. This data is mainly derived between 2017 and 2019. Due to the recent changes in the environment, the process may have differences. The findings perhaps give the outlines of the flow of the environmental auditing practices in the other organization. This further research may explore the effectiveness of the environmental auditing practices in MLGs and how the process shaped the character of the organizations